A randomized double-blind trial of intranasal dexmedetomidine versus intranasal esketamine for procedural sedation and analgesia in young children - Anna Nikula; Stefan Lundeberg; Malin Ryd Rinder; Mitja Lääperi; Katri Sandholm; Maaret Castrén; Lisa Kurland (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Procedural sedation and analgesia are commonly used in the Emergency Departments. Despite this common need, there is still a lack of options for adequate and safe analgesia and sedation in children. The objective of this study was to evaluate whether intranasal dexmedetomidine could provide more effective analgesia and sedation during a procedure than intranasal esketamine. Methods This was a double-blind equally randomized (1:1) superiority trial of 30 children aged 1–3 years presenting to the Emergency Department with a laceration or a burn and requiring procedural sedation and analgesia. Patients were randomized to receive 2.0 mcg/kg intranasal dexmedetomidine or 1.0 mg/kg intranasal esketamine. The primary outcome measure was highest pain (assessed using Face, Legs, Activity, Cry, Consolability scale (FLACC)) during the procedure. Secondary outcomes were sedation depth, parents’ satisfaction, and physician’s assessment. Comparisons were done using Mann–Whitney U test (continuous variables) and Fisher’s test (categorical variables). Results Adequate analgesia and sedation were reached in 28/30 patients. The estimated sample size was not reached due to changes in treatment of minor injuries and logistical reasons. The median (IQR) of highest FLACC was 1 (0–3) with intranasal dexmedetomidine and 5 (2–6.75) with intranasal esketamine, (p-value 0.09). 85.7% of the parents with children treated with intranasal dexmedetomidine were “very satisfied” with the procedure and sedation compared to the 46.2% of those with intranasal esketamine, (p-value 0.1). No severe adverse events were reported during this trial. Conclusions This study was underpowered and did not show any difference between intranasal dexmedetomidine and intranasal esketamine for procedural sedation and analgesia in young children. However, the results support that intranasal dexmedetomidine could provide effective analgesia and sedation during procedures in young children aged 1–3 years with minor injuries. Trial registration: Eudra-CT 2017-00057-40, April 20, 2017. https://eudract.ema.europa.eu/